Developing linguistic research tools for virtual lexicographic laboratory of the spanish language explanatory dictionary - Kupriianov, Yevhen; Akopiants, Nunu (Ruzica Piskac, 2019)
The present article is devoted to the problems of creating linguistic tools for the virtual lexicographic laboratory of Spanish explanatory dictionary (DLE 23). The goal of the research is to consider some issues related to the development of linguistic tools for the virtual lexicographic laboratory. To achieve this goal the dictionary was analyzed to define the peculiarities of linguistic facts representation, its structure and metalanguage. On the basis of the dictionary analysis and the theory of lexicographic systems the formal model of DLE 23 was developed and its main components, including their relationships, were determined to ensure their availability via linguistic tools for accessing linguistic information. The range of research activities to be performed by using the linguistic tools was outlined.
Keywords: computer lexicography; virtual lexicographic laboratory; digital environments; electronic dictionaries